PENGARUH PENERAPAN MODEL PBL TERHADAP KREATIVITAS DAN KETERAMPILAN BERKOMUNIKASI TERTULIS SISWA - Zhakia El Shinta; Berti Yolida; Rini Rita Marpaung (Universitas Lampung, 2015)
The purpose of this research was to know the influence of PBL towards students creativity and written communication skill. The research used pretest-posttest non equivalent design. The samples were students of VII A and VII D SMP Kartika II-2 that were chosen by purposive sampling technique. The quantitative data were obtained from creative thinking skill (Process dimension) that analyzed by using T-test and U-test. The qualitative data was students creative thinking skill, creative attitude (Person and Press dimension), creative product (Product dimension), and written communication skill that analyzed descriptively.The result showed criteria of experiment students creativity was in